An Integrative Approach to Determinants of Pre-Roll Ad Acceptance and Their Relative Impact: Evidence from Big Data. Issue 1 (25th April 2022) - Lee, Mi Hyun; Kim, Su Jung; Yoon, Sang-Hyeak; Park, Sungho
Abstract: Skippable ads are known to provide better advertising experiences by giving viewers a sense of control with the ability to skip an ad after watching it for a few seconds. Despite the growing interest, few studies have investigated factors that influence skipping or viewership of pre-roll skippable ads. This study examines the determinants of pre-roll ad acceptance by using clickstream data of 2, 078, 090 users' ad and content viewing behaviors on a popular online video content platform in South Korea. We found that skippable ad acceptance is impacted by personal, situational, and contextual factors that influence the level of goal impediment in online video consumption contexts. We conclude with theoretical and practical implications of the findings.